MANAJEMEN PELAKSANAAN BIMBINGAN DAN KONSELING MELALUI MEDIA KOTAK MASALAH DI ERA DIGITALISASI PENDIDIKAN - Radya Putri Novitasari; Luluk Muflikhatin; Dwi Lutviani Septianingtyas (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2026)
This study aims to analyze the application of management of the implementation of guidance and counseling through problem box media as an innovation in the era of education digitalization. This study explores how the function of POAC (Planning, Organizing, Actuating, Controlling) management to improve the efficiency, effectiveness, and accessibility of guidance and counseling services. The method used in this study is a literature study, which is carried out by the researcher to receive valid data based on the type of literature, including books, journals, and relevant scientific articles. In the era of education digitalization, the application of the POAC management function in guidance and counseling through problem box media allows the creation of more efficient, effective, and easily accessible services. Guidance and counseling programs are designed according to the needs of students through structured planning, optimal resource management, responsive implementation, and continuous supervision. Problem box media is a means that supports the achievement of academic goals and student development through the maximum use of technology.